(untitled) (Research, Society and Development, 2022)
Great social changes are happening worldwide with globalization; education has a fundamental role in forming critical subjects who know how to put themselves before society and its changes, aware of their rights and duties. From the era of technology and information, the methodologies addressed by higher education teachers end up being questioned, since their role is to train active subjects in society. Given this context, the present research aims to reflect on the use of active methodologies in higher education, how it is worked by teachers and how, if it facilitates the process of teaching learning. This is a qualitative research, carried out through the bibliographic review. The development of the present research made possible an analysis on the use of active methodologies Higher Education, starting from a reflection on the changes in pedagogical practice throughout the time, it was also possible to describe how these methodologies have been used, highlighting the importance of the same in the process of teaching learning.